Anniversary Resolutions of the Polish Sejm and Senate as the Subject of Political Science Research - Secler, Bartłomiej (Przegla̦d politologiczny, 2023)
Undoubtedly, memory studies can be included in the mainstream of contemporary political science. They encompass reflections on the politics of memory, and historical or collective memory. The political science literature has designated little space to examine anniversary resolutions of the Polish Sejm and Senate after 1989. Therefore, it has become the main focus of this article based on research conducted and funded by the National Science Centre. The research examined the place and role of anniversary resolutions of the Polish Sejm and Senate in the Polish politics of memory. It has been assumed that such resolutions express the will of the two chambers of the Polish Parliament to commemorate historical anniversaries related to events and people who, in the opinion of resolution promoters, play an important role in the history of the state and nation. Furthermore, it is understood that the anniversary resolutions, among other things, are an important tool of the authorities to implement the politics of memory. The aim of the publication is to present the main research findings. The findings are based on the analysis of 589 anniversary resolutions adopted by the Sejm and the Senate in 1989–2019. The article also draws attention to the significance and usefulness of the resolutions for political science research, not only those referring to memory studies.